If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12X + 7X = 13 Combine like terms: -12X + 7X = -5X -5X = 13 Solving -5X = 13 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Divide each side by '-5'. X = -2.6 Simplifying X = -2.6
| -3r*4rx+x+12= | | -5=C-10 | | 15n^2-30n=0 | | 9(t-3)+36t=6(t+2) | | 3-(x-4)=2x+5 | | 12s^3+22s^2-70s=0 | | [10-5(x-2)]=(x+1) | | 5+5w=2+11w | | 6x-3=15-48 | | 3/x=9/2 | | 7/8*h=1/5 | | 35u^2-39u-14=0 | | 10.1+5.3=w | | 1=y(8y-4) | | 1,34x-5,4=x-3,7 | | 2*2=5y | | X^2+18+20=0 | | 4x=y(4x-4) | | -(14-2s)-(6s+4)=14 | | 4x^3+14x^2+166x+140=0 | | 4xy-4y-4x=0 | | 5r^2-6r+1=0 | | (31-0.5y)+(31-0.5y+4)+y=66 | | y=70+14(7) | | 2*40+3x=128 | | 73=x+0.32x | | 6x+ay=24 | | 2x+9x-4x=14+7 | | 0.03/9 | | 3x+ay=15 | | -2t^2+15t-15=0 | | x*x-v*v= |